2016
DOI: 10.18632/oncotarget.8212
|View full text |Cite
|
Sign up to set email alerts
|

An individualized prognostic signature and multi-omics distinction for early stage hepatocellular carcinoma patients with surgical resection

Abstract: Previously reported prognostic signatures for predicting the prognoses of postsurgical hepatocellular carcinoma (HCC) patients are commonly based on predefined risk scores, which are hardly applicable to samples measured by different laboratories. To solve this problem, using gene expression profiles of 170 stage I/II HCC samples, we identified a prognostic signature consisting of 20 gene pairs whose within-sample relative expression orderings (REOs) could robustly predict the disease-free survival and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…Using the REOs of HCC‐specific gene pairs from comparisons with the six cancer types, we found that eight of 24 HCC cell lines collected from the Cancer Cell Line Encyclopedia (CCLE) resemble HCC tumours well, whereas the other 16 HCC cell lines are closer to at least one of the six cancer types than to HCC itself. In addition, we showed that all of the confirmed eight HCC cell lines are likely to be metastatic, based on a REO‐based prognostic signature for early stage HCC patients . In short, this study provides a helpful guide to select proper HCC cell lines as models for HCC.…”
Section: Introductionmentioning
confidence: 71%
“…Using the REOs of HCC‐specific gene pairs from comparisons with the six cancer types, we found that eight of 24 HCC cell lines collected from the Cancer Cell Line Encyclopedia (CCLE) resemble HCC tumours well, whereas the other 16 HCC cell lines are closer to at least one of the six cancer types than to HCC itself. In addition, we showed that all of the confirmed eight HCC cell lines are likely to be metastatic, based on a REO‐based prognostic signature for early stage HCC patients . In short, this study provides a helpful guide to select proper HCC cell lines as models for HCC.…”
Section: Introductionmentioning
confidence: 71%
“…Here, we applied RMOs procedure in the construction of the prognosis methylation signature. The prognostic signature base on RMOs is robust against experimental batch effects and data normalization, and can be easily applied at the individual level to sample which are measured in different laboratories [13]. We performed Cox regression variable analyses to further investigate the association between RFS with candidate gene pairs and the 9-gene-pair signature.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the prognosis ability of this score is better than any individual candidate gene pair. This further emphasized the importance of developing a comprehensive signature for cancers [13]. We also performed multivariable Cox regression to estimate the association between RFS and the signature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations